FORTIFIKASI GUAVA (Psidium guajava L.) JELLY DRINK DENGAN ZAT BESI ORGANIK DARI KEDELAI (Glycine max L.) DAN KACANG HIJAU (Vigna radiate L.) - Christina Hanny Setyaningrum; Ivone Elizabeth Fernandez; Robertus Probo Yulianto Nugrahedi (Faculty of Agricultural Technology, University of Jember, 2017)
Anemia is a condition of haemoglobin level that is below normal. One of the major causes is lacking of iron consumption, which is important in haemoposis process. Compared to men, women have less total iron in the body, and it raises the risk of anemia. The main purpose of this research was the fortification of iron in beverage. This research used soybean and mungbean as source of iron, which known as non-heme iron. To improve the absorption, ascorbic acid was needed as an enhancer, using guava and was produced into guava jelly drink. Method for extraction process is by maseration with 30% etanol as solution. The value of iron extract assessed by AAS at 248,3 nm. The formula of fortification was 20% of RDA of iron for woman, which was 18 mg per day. Chosen product was evaluated by sensory test. The nutrition value of product assessed including iron content, ascorbic acid, and proximate composition. The iron content of soybean was 113,86 ppm and 58,76 for mungbean. The nutrition of guava jelly drink with addition of fortificant were 87,47% water, 0,35% ash, 0,2% fat, 0,31% protein, 11,67% carbohydrate, 130,48 ppm iron, and 90,79 mg ascorbic acid. Keywords: iron deficiency anemia, soy bean, mungbean, jelly drink, and guava